Attention and vigilance : a large scale workplace study - Roberts, Adam Charles (2020)
Many previous studies have examined the effect of working environment on job performance. However, these are usually site-specific experiments examining office workers, concentrating on self-report measures and peer assessments. An area of particular interest is whether computerised tests could be used to identify deficits in performance and associate these with specific environmental problems. We recruited over four hundred participants from several companies in Singapore, spanning a range of job types requiring different levels of visual attention, broadly grouped as technical workshop staff, office staff, and operational control room workers. Where possible, job types were matched across companies. Participants were given a series of psychological, environmental, and health-related questionnaires and computerised tests examining various aspects of visual attention (psychomotor vigilance task, go-nogo task and global-local change detection) as analogues of work performance. Mixed effect models were used to examine the workers’ performance, taking into account work-related, environmental, and health related factors. Results indicate variability across companies and job types, effects of shift work, and some effects of environment on vigilant and selective attention.